2020
DOI: 10.3390/ani10050769
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomics Revealed the Differential Metabolic Pathway in Calves with Severe Clinical Diarrhea Symptoms

Abstract: The complex etiology, higher morbidity and mortality, poor prognosis, and expensive cost of calf diarrhea have made it a catastrophic disease in the dairy industry. This study aims to assess the biomarkers in calves with diarrhea and to predict the biomarkers related to the pathway. As subjects, nine calves with diarrhea and nine healthy calves were enrolled, according to strict enrollment criteria. The serum metabolites were detected by a liquid chromatographic tandem mass spectrometry (LC-MS/MS), and then an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Only one paper has been published describing different metabolite profiles in perinatal mortality cases [102], but it investigated only metabolic profiles in calves with different times of death, irrespective of the cause. A recent study showed promising results using metabolic profiles in facilitating diagnosis and treatment of calves with diarrhea [103], but the number of animals was small and this work needs to be reproduced in a larger population. Also, in cases of bovine respiratory diseases, metabolic profiles could be used to identify sick animals correctly in the majority of cases [104].…”
Section: Fetal Metabolic Response-perspectivesmentioning
confidence: 99%
“…Only one paper has been published describing different metabolite profiles in perinatal mortality cases [102], but it investigated only metabolic profiles in calves with different times of death, irrespective of the cause. A recent study showed promising results using metabolic profiles in facilitating diagnosis and treatment of calves with diarrhea [103], but the number of animals was small and this work needs to be reproduced in a larger population. Also, in cases of bovine respiratory diseases, metabolic profiles could be used to identify sick animals correctly in the majority of cases [104].…”
Section: Fetal Metabolic Response-perspectivesmentioning
confidence: 99%
“…Few research on multi-omics techniques focused on calf diarrhea. Recently, metabolomics was used to study the mechanism of diarrhea in calves, and acetylcarnitine, indoxyl sulfate, and oxindole have been recognized to be potential biomarkers for calf diarrhea ( 11 ). Additionally, metabolites such as lecithin and choline have been found to affect the progression of DHD by interfering with the metabolism of arachidonic acid, linoleic acid, and glycerophospholipids in calves ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, LC-MS technology enables high-level separation and characterization of metabolites, thereby providing accurate (semi-)quantification and identification [ 14 ]. On the subject of calves’ disease, metabolomics has already been performed, although solely focusing on plasma and/or serum and implementing targeted metabolomics [ 7 , 15 , 16 , 17 , 18 ]. These particular studies assessed diarrhea, BRD, and sepsis in calves, whereby creatine, choline, acetate, lysine, 2-methylglutarate, allantoin, and phenylalanine were ascertained to be significantly affected by health state and therefore introduced as potential biomarkers.…”
Section: Introductionmentioning
confidence: 99%